Isotopes ratio investigation in soil samples from 5-km ChNPP zone - M. V. Zheltonozhska (Âderna Fìzika ta Energetika, 2009)
Isotope ratios of 134,137Сs and 154,155Eu were measured in the vertical profiles of the soils of 5-km nearest ChNPP zone and in the FCM samples from 4-th unit of the ChNPP. The increasing of the 134Сs (20 - 25%) in the first layers was detected in some vertical soil profiles. Possible existence of fuel component with different burnout can explain this fact. This factor changes the ecological periods of semidepuration of upper layers of soils.